THE EFFECT OF CUSTOMER SATISFACTION, CUSTOMER LOYALTY, AND BRAND COMMITMENT ON WORD OF MOUTH OF WALL’S ICE CREAM IN MANADO - Kindangen, Citra Pingkan; Pandowo, Merinda Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Food and beverage products and the followed improvement in industry are familiar for common people in every part of this world. The aim of this research is to analyze the effect of customer satisfaction, customer loyalty, and brand commitment on word of mouth. To achieve the objectives, the research method used is causal research by using multiple regression analysis as the analytical tool. The population of this research is the consumers in Manado who ever taste wall’s Ice cream with sample size as many as 120 respondents. This research found that customer satisfaction, customer loyalty and brand commitment generally give the significant influence for word of mouth of wall’s ice cream in Manado. Customer satisfaction, customer loyalty and brand commitment have significant influence for the changing of the significant influence for the word of mouth of wall’s ice cream. This research suggests that the management must give the in-depth consideration about the importance of customer satisfaction, customer loyalty and brand commitment for the word of mouth in purchasing its products and the management must also give concern about other important factors that can influence the word of mouth for ice cream products from this company.Keywords: customer satisfaction, customer loyalty, brand commitment, word of mouth.